2021
DOI: 10.1038/s41467-021-22872-z
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal single-cell profiling reveals molecular heterogeneity and tumor-immune evolution in refractory mantle cell lymphoma

Abstract: The mechanisms driving therapeutic resistance and poor outcomes of mantle cell lymphoma (MCL) are incompletely understood. We characterize the cellular and molecular heterogeneity within and across patients and delineate the dynamic evolution of tumor and immune cell compartments at single cell resolution in longitudinal specimens from ibrutinib-sensitive patients and non-responders. Temporal activation of multiple cancer hallmark pathways and acquisition of 17q are observed in a refractory MCL. Multi-platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 73 publications
4
50
0
3
Order By: Relevance
“…To gain insight into this heterogeneity at single cell level, we performed single cell mRNA sequencing of the purified CD19 + fraction of diagnostic bone marrow aspirates from eight MCL patients. The inter-tumor heterogeneity was striking as previously reported in MCL 47 . However, in contrast to the subclonal involvement, as shown on unsorted mononuclear cells by two recent scRNA-seq studies 47 , 48 , the transcriptional profiles observed in this study were rather unremarkable with a homogeneous continuum of expression patterns observed for the malignant cells.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…To gain insight into this heterogeneity at single cell level, we performed single cell mRNA sequencing of the purified CD19 + fraction of diagnostic bone marrow aspirates from eight MCL patients. The inter-tumor heterogeneity was striking as previously reported in MCL 47 . However, in contrast to the subclonal involvement, as shown on unsorted mononuclear cells by two recent scRNA-seq studies 47 , 48 , the transcriptional profiles observed in this study were rather unremarkable with a homogeneous continuum of expression patterns observed for the malignant cells.…”
Section: Discussionsupporting
confidence: 82%
“…The inter-tumor heterogeneity was striking as previously reported in MCL 47 . However, in contrast to the subclonal involvement, as shown on unsorted mononuclear cells by two recent scRNA-seq studies 47 , 48 , the transcriptional profiles observed in this study were rather unremarkable with a homogeneous continuum of expression patterns observed for the malignant cells.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In line with this, leukemia samples as well as lymphoma cells circulating in the peripheral blood were the subjects in hematology-focused projects of early days [ 26 , 27 ], with acute myeloid leukemia (AML) being the most frequently published oncohematological entity [ 28 ]. To date, SCS datasets have been generated for a wide range of blood cancers, including chronic myeloid leukemia [ 29 ], myeloproliferative neoplasms [ 30 , 31 ], myelodysplastic syndrome/acute myeloid leukemia [ 21 , 27 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], acute lymphoblastic leukemia (ALL) [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], chronic lymphocytic leukemia [ 59 , 60 , 61 ], mantle cell lymphoma [ 61 , 62 , 63 ], follicular lymphoma [ 61 , 64 , 65 , 66 ], diffuse large B-cell lymphoma [ 61 ], multiple myeloma [ 26 , 67 ], Hodgkin lymphoma […”
Section: Introductionmentioning
confidence: 99%
“…advance for patients with refractory MCL. But despite these advances, drug resistance 15 and frequent relapses occur, and MCL remains incurable.…”
mentioning
confidence: 99%